2007 Farm Bill: Attitudes of Specialty Crop Growers to Alternative Policy Options - John J. VanSickle; Richard Weldon (EDIS)
FE674, a 5-page fact sheet by John VanSickle and Richard Weldon, summarizes the results of a survey of specialty crop growers in Florida, to assess the knowledge and attitudes of growers on the 2002 Farm Bill, and their needs for the 2007 Farm Bill. Includes references. Published by the UF Department of Food and Resource Economics, October 2006.